2018
DOI: 10.1002/jcp.27922
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stem cells for wound healing

Abstract: Wound healing is a complex but a fine‐tuned biological process in which human skin has the ability to regenerate itself following damage. However, in particular conditions such as deep burn or diabetes the process of wound healing is compromised. Despite investigations on the potency of a wide variety of stem cells for wound healing, adipose‐derived stem cells (ASCs) seem to possess the least limitations for clinical applications, and literature showed that ASCs can improve the process of wound healing very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 161 publications
(250 reference statements)
0
124
0
Order By: Relevance
“…A series of studies have uncovered the probable pathophysiology of diabetic wounds, which includes decreased growth factor production, impaired angiogenesis and defective cellular functions in the impaired wound [26]. The current conventional treatments, such as application of dressings, negative pressure therapy, autologous skin graft and hyperbaric oxygen therapy, have several limitations and moderate efficacy [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies have uncovered the probable pathophysiology of diabetic wounds, which includes decreased growth factor production, impaired angiogenesis and defective cellular functions in the impaired wound [26]. The current conventional treatments, such as application of dressings, negative pressure therapy, autologous skin graft and hyperbaric oxygen therapy, have several limitations and moderate efficacy [7].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that stem cell therapy can contribute to diabetic wounds and other diseases [4][5][6]. Compared with other types of stem cells, adipose-derived stem cells (ADSCs) have specific advantages and fewer limitations; they are abundant and easily harvested, can be delivered via a minimally invasive procedure, are associated with fewer ethical issues and have less risk of inducing tumorigenicity and the host immune response [7,8]. A large number of studies have verified the therapeutic efficacy of ADSCs for wound healing [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focused on skin wound healing. Stem cells were used to cure wound healing [5]. In our study, BMSCs and HSCs were used to cure wound healing in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells and hematopoietic stem cells are often injected in blood or around the wound. However, these methods have di culties in tissue targeting and high cell attrition rate [5]. Very few studies had shown bone mesenchymal stem cells(BMSC) and hematopoietic stem cells(HSC) could arrive to the wound and differentiate into tissues [6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with bone marrow-derived stem cells (BMSCs), hADSCs are favored in stem cell therapy for their advantages in terms of expansion ability, easy of isolation, and survival rate during culturing. Therefore, hADSCs have been considered as an attractive cell type for MSC transplantation therapy in regenerative medicine [16][17][18].…”
Section: Introductionmentioning
confidence: 99%